Representation of Moral Values in Elt Textbook “Work in Progress” for 10th Grade Students of Senior High School - Ariska Dwi Purwanti (Faculty of Teacher Training and Education, 2026)
Moral values are an important aspect of students’ character development. One medium that plays a role in representing these values is the English textbook, through the visual elements it contains. However, previous research has focused primarily on textbooks based on the 2013 Curriculum and has not yet comprehensively examined the representation of moral values in the visual artifacts of the “Work in Progress” textbook for 10th-grade high school students using the ideational metafunction within the framework of Systemic Functional Linguistics (SFL). This study employed a qualitative descriptive method by analyzing 24 visual artifacts using documentation techniques. The results show that all dimensions of the Pancasila Student Profile have been represented, although their distribution remains uneven. Therefore, teachers are encouraged to optimize the use of visual artifacts in instruction, while textbook developers need to present representations of moral values in a more balanced manner to support the strengthening of character education.
Validasi dan Finalisasi Repositori File 29Juni 2026_Kholif Basri
Keywords: SOCIAL SCIENCES::Social sciences::Education; Moral Values; Textbook; Visual Artifacts